IMPLEMENTATION OF COLLABORATIVE GOVERNANCE IN THE DEVELOPMENT OF MSME DIGITALIZATION IN THE ERA OF SOCIETY 5.0 - Rose Diana; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of collaborative governance in the development of digitalization of Micro, Small, and Medium Enterprises (MSMEs) in the Society 5.0 era. MSME digitalization is a crucial strategy for increasing the economic competitiveness of communities amidst the increasingly rapid development of information and communication technology. However, the digitalization process cannot be carried out independently by MSMEs, requiring collaboration between the government, the private sector, academics, and the community. This study used a qualitative method with a descriptive approach through a literature review of various journals, books, and scientific documents related to collaborative governance and MSME digitalization. The results show that the implementation of collaborative governance can create synergy between actors in increasing MSME capacity through digital training, technology-based marketing, and strengthening digital market access. Supporting factors for the success of collaborative governance include effective communication, shared commitment, and technological support. Meanwhile, obstacles identified include low digital literacy, limited infrastructure, and minimal participation of some MSMEs. This study concludes that collaborative governance plays a strategic role in supporting the development of MSME digitalization in the Society 5.0 era.